UPAYA MEMBANGUN KARAKTER BANGSA MENCEGAH RADIKALISME DAN TERORISME DI INDONESIA - Markum; Winarno (Jurnal PPKn, 2020)
Today there are 2 (two) threats faced by the Indonesian people, namely 1) the decline in living out of the values ??of Pancasila in the life of the nation and state, and 2) the existence of radicalism that leads to violence and terrorism. This study wants to explain how the role of the government as state organizer in anticipating threats as an effort to build the nation's character. Data sources from literature study, relevant current news and interviews with several experts. Data analysis was performed interactively and presented qualitatively descriptive. The study's findings show that the role of government in building the nation's character is carried out through various activities and instruments that accompany it. Pancasila ideology guidance has been provided, for example with the PPKn lessons and the establishment of the Pancasila Odeology Development Board (BPIP). Efforts to prevent acts of radicalism and terrorism are through preventive and repressive activities and de-radicalization programs developed in order to minimize the development of radical attitudes and understandings through the establishment of the National Counterterrorism Agency (BNPT).   Full Paper